Operatic album containing six song for contralto voice selected from standard and modern operas Book I4 - VERDI [et.al] (G. Ricordi)
Vi ravviso, o laughi ameninSi la rigueur et la vengeancenVecchia zimarra, sentinElla giammai m'amonLe veau d'or est toujours deboutnVous qui faites l'enormie